2012
DOI: 10.3851/imp2310
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase I Bioequivalence Clinical Trial of a Paediatric Fixed-Dose Combination Antiretroviral Reconstitutable Suspension in Healthy Adult Volunteers

Abstract: This single dose randomized study found that the test and reference products met the criteria for bioequivalence in the fasting healthy adult volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Although the BE studies are widely being conducted all over the world, a research on overall adverse event specific evaluations were not found. Research on the adverse reactions as a post-marketing safety survelliance often takes place in the scientific literature (Lazarou et al 1998 ; Sibille et al 1998 ; Baker et al 2004 ) while BE studies were mostly focused on the pharmacokinetics, assessing the relationship between genetic polymorphisms, and safety issues of the single test (generic) and reference (originator) drugs (Zhang et al 2006 ; Zhang et al 2007 ; Cho et al 2009 ; Esseku et al 2013 ; Gao et al 2015 ; Mak et al 2015 ). Therefore, our study has the originality by revisiting the BE studies of 13 years period belonging to one of the CRO’s database (N-CRO) in Turkey, regarding the frequency, type, drug subgroups, cut off (split points using Gini Index) values and probable causes of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Although the BE studies are widely being conducted all over the world, a research on overall adverse event specific evaluations were not found. Research on the adverse reactions as a post-marketing safety survelliance often takes place in the scientific literature (Lazarou et al 1998 ; Sibille et al 1998 ; Baker et al 2004 ) while BE studies were mostly focused on the pharmacokinetics, assessing the relationship between genetic polymorphisms, and safety issues of the single test (generic) and reference (originator) drugs (Zhang et al 2006 ; Zhang et al 2007 ; Cho et al 2009 ; Esseku et al 2013 ; Gao et al 2015 ; Mak et al 2015 ). Therefore, our study has the originality by revisiting the BE studies of 13 years period belonging to one of the CRO’s database (N-CRO) in Turkey, regarding the frequency, type, drug subgroups, cut off (split points using Gini Index) values and probable causes of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical batch of the test product was manufactured by Emerson Resources Inc. (Norristown, Pennsylvania) Xylitol, sucralose, microcrystalline cellulose, carboxymethylcellulose sodium, colloidal silicon dioxide, methylparaben, and propylparaben were used as excipients. The 90% CI for the geometric mean ratio of test/reference for C max , AUC 0– t , and AUC 0– ∞ for lamivudine, zidovudine, and nevirapine were within the 80%–125% BE limits 92…”
Section: Dosage Form Performancementioning
confidence: 80%
“…The 90% CI for the geometric mean ratio of test/reference for C max , AUC 0-t , and AUC 0-∞ for lamivudine, zidovudine, and nevirapine were within the 80%-125% BE limits. 92…”
Section: -876 Amentioning
confidence: 99%
“…A total of 800 μl of clear supernatant liquid was evaporated under nitrogen at 37 °C, and the solid residue thus obtained was dissolved in 25 m m potassium phosphate buffer and analysed by HPLC. The detailed method including the drug extraction and validation is reported elsewhere . The chromatograms were extracted for each sample, and ratio of the peak area of drug to the internal standard was evaluated against the calibration samples to estimate the drug concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed method including the drug extraction and validation is reported elsewhere. [20,21] The chromatograms were extracted for each sample, and ratio of the peak area of drug to the internal standard was evaluated against the calibration samples to estimate the drug concentrations.…”
Section: Bioanalytical Assaymentioning
confidence: 99%